APPLICATION OF PAVLIK HARNESS IN DEVELOPMENTAL DYSPLASIA OF THE HIP (DDH) - Aryadi Kurniawan; Ahmad Fauzi (Fakultas Kedokteran Universitas Lampung, 2014)
Developmental dysplasia of the hip (DDH) is a spectrum of pathology ranging from acetabular dysplasia with minor instability until acetabular dysplasia with hip dislocation. The incidence of DDH that require treatment is 5.1 per 1000 live birth. Early detection is important to deliver good outcome and lessen complication. Careful history taking, physical examination and ultrasonography, have increased the sensitivity in establishing diagnose of DDH. Pavlik harness is the mainstay of treatment for infant who has not commenced crawling. Despite the fact of high success rate, the use of Pavlik harness is still uncommon in Indonesia. This paper reports a case of DDH treated with Pavlik harness and assessed regularly with ultrasonography. A 3 months girl with developmental dysplasia of the left hip. The initial ultrasound shows α angle 49.40 and β angle was 50.20, femoral head subluxated to superolateral aspect. The patient had Pavlik harness and followed up with serial ultrasound at 1st, 3rd and 4th month’s time. Having had 4 months of Pavlik harness, the α angle of the left hip became 630, and β angle 490 with good structure of ilium. Femoral head was smooth and no signs of avascular necrosis. The hip has full range of motion. Parents have no difficulty in taking care of their daughter daily activities such as taking a bath, changing napkin, and clothes. This implicates, patient treated using Pavlik harness showed good outcome clinically and ultrasonographically. Pavlik harness has been proven to be a safe, simple and user friendly method for treatment of DDH before crawling age. The good result obtained from this case could initiate application of pavlik harness in larger population of early detected DDH in Indonesia. [JuKe Unila 2014; 4(8):208-217]